Counseling : an indigenous perspective - Ivey, Allen E.; Ivey, Mary Bradford; Oldershaw, Bruce, 1931- (Counseling and therapy in video, volume 1, 1998)
Allen Ivey (with Mary Bradford Ivey) interviews David Rathman, Chief Executive Officer of Aboriginal Affairs, South Australia, regarding his views on counseling in a cross-cultural context, representing the views of many indigenous peoples throughout the world.